Pengaruh Tingkat Pendapatan Terhadap Kesadaran Membayar Pajak Bumi dan Bangunan (Studi Kasus Desa Tanjungwangi Kec. Pacet Kab. Bandung) - Arini, Novia Suci; Feriyanto, Oon (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This This study aims to determine the influence of income level on the awareness of Land and Building Tax (PBB) taxpayers in Tanjungwangi Village. The research employed a quantitative method with a descriptive approach and simple linear regression analysis. A total of 95 respondents were selected using purposive sampling. The analysis results indicate that income level has a positive and significant effect on taxpayer awareness. This is demonstrated by the regression equation Y = 6.555 + 0.431X, with a coefficient of determination (R²) of 0.657, meaning that income level contributes 65.7% to taxpayer awareness, while the remaining 34.3% is influenced by other factors. The t-test shows a significance value of 0.000 and a t-count of 13.354, which is greater than the t-table value, indicating that the hypothesis is accepted. Therefore, the higher the income level, the higher the taxpayer’s awareness in fulfilling their tax obligations.